Digital sovereignty. A new key concept of digital policy in Germany and Europe - Julia Pohle (Konrad-Adenauer-Stiftung, 2020)
Striving to strengthen digital sovereignty, self-determination and strategic autonomy has become a cornerstone of German and European digital pol icy. Within Germany and Europe there are diverging notions of digital sovereignty. However, a common or at least consistent understanding of what is meant by this or what its associated requirements are, has yet to emerge. In particular – but not exclusively – in the political sphere, we can see that this concept is tied to various interpretations and associations. The many different meanings attached to the concept of digital sovereignty in Germany and Europe could be broken down and categorized in three levels, within which a strengthening of digital sovereignty is strived for. These are the state, the economy and the individual. There are always considerable conflicts of interest between these dimensions of digital sovereignty. Between these dimensions, conflicts of political objectives arise that cannot be resolved. In order to leverage the potential inherent in the concept of digital sovereignty for a more strategic and holistic digital policy, not only conceptual work and political will is required. It is also necessary to reflect on what a liberal and democratic understanding of sovereignty actually stands for in the digital age.
Keywords: 300